How Hearding Behaviour and Financial Literacy affect Young People's Investment Decisions - Natasya Puspitarini; Maretha Ika Prajawati; Basir S (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research aims to analyze the influence of herding behavior and financial literacy on investment decisions. Investment decisions are the main key for someone to achieve their goal, namely maximizing profits. The decisions taken should be in accordance with the risk that will be accepted and the level of return. When novice voters start an investment, other people's opinions are often taken into consideration when making decisions, which is known as herding behavior. And when choosing an investment, we need to learn about financial literacy to avoid fraudulent investments. A questionnaire was given to 77 respondents as part of the quantitative research methodology. There will be four tests used to evaluate the results: the validity test, reliability test, t test, and f test. The test's findings showed that financial knowledge and herding tendency both significantly influenced investing choices. According to the findings, financial knowledge and herding tendency significantly influence investment choices.